Analysis Of Press Ethics News Issue "Luhut Reported To The South Sulawesi Police Regarding Big Data Postponement Of Elections" On Online News Media Cnnindonesia.Com - Rio Rizky Koara; Johantan Alfando Wikandana Sucipta (Eduvest - Journal of Universal Studies, 2024)
The purpose of this research is to find out how  to frame the news issue "Luhut Reported To The South Sulawesi Police Regarding Big Data Postponement Of Elections" in CNNIndonesia.com? This study uses a descriptive qualitative research method. Descriptive research aims to provide an overview and description of the observed phenomenon, in this case an analysis of press ethics on news issues. Descriptive research will focus on systematic data collection and analysis, so that it can provide detailed information about the characteristics, behaviors, or other aspects of the phenomenon being studied. As a result, CNN Indonesia should verify any claims that arise as an issue and ensure that the information presented is accurate and not misleading.